Evaluate the Therapeutic Effect of Allicin (L-cysteine) on Clinical Presentation and Prognosis in Patients with COVID-19 - Hosein Yaghoubian; Hossein Niktale; Arash Peivandi Yazdi; Vahideh Ghorani; Masoud Mahdavi Rashed; Amir Masoud Hashemian (PAGEPress Publications, 2021)
The antiviral effectiveness of allicin (L-cysteine) has been shown by numerous studies in both levels of clinical and animals. The aim of this study was to evaluate the therapeutic effect of allicin (L-cysteine) on clinical presentation and prognosis. In the current study, 66 patients with COVID-19 based on clinical, radiological presentations and RT-PCR results, were enrolled in two groups of placebo and allicin. In the both allicin (L-cysteine) and placebo groups (n=33 in each group), the capsules were prescribed two times a day for two weeks. Clinical signs and symptoms, blood parameters and chest CT scan were evaluated before and two weeks after treatment. The results showed that allicin (L-cysteine) could significantly impact on improvement of signs and symptoms of COVID-19 after two weeks of treatment in comparison to placebo. Allicin (L-cysteine) not only improve the clinical signs, but also ameliorate the lab and radiological data, which suggest a therapeutic effect for this agent in COVID-19. Our data suggest the therapeutic effect of allicin (L-cysteine) on COVID-19 through improvement of clinical symptoms and acceleration of the healing process.